Enhancing Polylactic Acid (PLA) Performance: A Review of Additives in Fused Deposition Modelling (FDM) Filaments - Plamadiala, Ioan; Croitoru, Catalin; Pop, Mihai Alin; Roata, Ionut Claudiu (MDPI- Polymers, 2025)
This review explores the impact of various additives on the mechanical properties of polylactic acid (PLA) filaments used in Fused Deposition Modeling (FDM) 3D printing. While PLA is favored for its biodegradability and ease of use, its inherent limitations in strength and heat resistance necessitate enhancements through additives. The impact of natural and synthetic fibers, inorganic particles, and nanomaterials on the mechanical properties, printability, and overall functionality of PLA composites was examined, indicating that fiber reinforcements, such as carbon and glass fibers, significantly enhance tensile strength and stiffness, while natural fibers contribute to sustainability but may compromise mechanical stability. Additionally, the inclusion of inorganic particulate fillers like calcium carbonate improves dimensional stability and printability, although larger particles can lead to agglomeration issues. The study highlights the potential for improved performance in specific applications while acknowledging the need for further investigation into optimal formulations and processing conditions.
Keywords: PLA; mechanical properties; additives; carbon fiber; glass fiber; additive manufacturing; graphene; CNT